An improved data-based algorithm for choosing the window width when estimating the density at a point - Sheather, Simon J. (Computational statistics & data analysis, 1986)
Sheather [3] proposed a data-based algorithm for choosing the window width when estimating the density at a point by a kernel estimator. Unfortunately, for some densities the windows widths produced by the algorithm have considerable bias. More importantly the resulting density estimator is not scale invariant. In this note we show how a modification to the algorithm overcomes these two problems.